Mediating role of innovation strategy between porter's red ocean strategy and innovative performance - Muhammad, Shafiq; Tasmin, Rosmaini; Mehwish, Rashid (American Scientific Publishers, 2017)
Competitive advantage is need of every organization in today’s business environment especially when competition is very tough. This enforces organizations to make strategies to be more innovative for survival and progress. In today’s fast paced word of knowledge, strategies for business are characterized in Red oceans of competition and Blue oceans of uncontested markets. This paper exclusively tries to look into porter’s red ocean business strategy though generally there are different Red Ocean strategies of competitive market, these strategies are Porter’s competitive forces strategy, Resource based theory, and ‘Miles and Snow’ strategies etc. Though there are many studies on relationship of strategy and innovation but very few empirical studies are available. This paper examines the influence of porter’s business strategies of differentiation and cost on organizational innovation performance. This paper also explores that how porter’s red ocean strategy performs better for innovative performance. Mediating role of Open innovation strategy is also discussed. These relationships for innovation performance will be explored for other red ocean strategies and Blue Ocean Strategy in other papers. For this purpose, we shall use a quantitative research design and will collect data from 250 SME’s in Malaysia through a self-administrated questionnaire. Results will be analyzed for the relationship of porter strategy of cost and differentiation with innovation performance, moreover the mediating effect of Open innovation will be explored between porter’s ROS and Innovation performance.